Mediterranean university campuses enhance butterfly (Lepidoptera) and beetle (Coleoptera) diversity - Arjona, José Manuel; Ibáñez-Álamo, Juan Diego; Sanllorente, Olivia (Frontiers in Ecology and Evolution, 2023)
Human population growth is causing an expansion of urban areas, a phenomenon known to deeply impact on the Earth’s biodiversity. Therefore, it is key to understand how to conceal urban development with biodiversity conservation. In this context, university campuses can play an important role as they usually present a large array of different environments and green areas, crucial aspects for promoting urban biodiversity as well as human-nature interactions. Several studies have analyzed the biodiversity of university campuses, however, there are still important taxonomic (e.g., insects) and geographical biases (e.g., Mediterranean hotspot) in our current understanding of these urban areas. Insects are fundamental in many ecosystems as pollinators, prey, pest controllers or decomposers among others. This further increases the need to study this group in the urban context. In this study, we have investigated diurnal Lepidoptera and ground-dwelling Coleoptera in three university campuses and three non-campus areas of the city of Granada (Spain). We used spatial and temporal replicates for each area in order to explore whether university campuses hold higher levels of insect biodiversity (e.g., species richness or common species) than other nearby urban areas. In addition, we investigated the potential influence of several additional predictors on insect diversity such as type of land cover, vegetation origin, management intensity, and distance to the outskirts. Our results suggest that Lepidoptera species and Coleoptera families are more diverse in university campuses than in other urban areas, showing also a positive association with the proportion of bare soil and herbaceous cover. Furthermore, they also seem to be benefited from low vegetation management intensity whereas Coleoptera are favored by native vegetation providing clear management recommendations in order to promote such animal groups in cities. Our study indicates that university campuses are important urban areas to preserve insect biodiversity but also highlights the heterogeneity of response among insect groups.